Dynamic Susceptibility Spectra of Superellipses-Shaped Nanostructures - Saavedra-Díaz, E (Institute of Physics, 2025)
Through numerical simulations, we delve into the examination of the equilibrium state and dynamic response of superellipses-shaped nanostructures. Within these nanostructures, we identify two distinct equilibrium states - in-plane magnetic configuration along the x-axis and vortex configuration. Our findings reveal a direct correlation between the number and frequencies of peaks with the minimum energy configuration, which is contingent upon the physical parameters of the system. This observation implies the potential to intentionally manipulate a desired set of frequencies by precisely controlling the geometric parameters of the system. © 2025 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.